(untitled) (American Journal of Multidisciplinary Research and Innovation, 2023)
Classroom management is one of the most important factors behind a successful learning experience. This article argues that classroom management is more complex than disciplinary problems and that both teachers and students should be engaged to improve the quality of the teaching/learning process. This article, thus, aims at investigating both teachers and students perspectives of classroom management in Moroccan public high schools. This study has sought to use interviews and observations to shed light on the details of an effective classroom management. This article uses chiefly qualitative methods to address the major methods teachers use to achieve an affective classroom management and the perspectives of students’ on what it means to study in an (un-)healthy learning environment. The results of fieldwork and interviews reveal that Moroccan public high schools’ teachers and students are in dire need of the improvement of communicative skills and planning, the renovation of the curricula, and the involvement students in the learning process. According to teachers and students, these are the key factors that would ensure an effective classroom management in Moroccan public high schools.